Does improved access to care affect utilization and costs for patients with chronic conditions? - Solberg, Leif I; Maciosek, Michael V; Sperl-Hillen, JoAnn M; Crain, A Lauren; Engebretson, Karen I; Asplin, Brent R; O'Connor, Patrick J (The American journal of managed care, 2004)
To determine whether a major improvement in access (ie, implementing an open access system) in a large multispecialty medical group during 2000 was associated with changes in utilization or costs for patients with diabetes, coronary heart disease (CHD), or depression. Multilevel regression analysis of health plan administrative data. Approximately 7000 patients with diabetes, 3800 with CHD, and 6000 with depression who received all of their care in this care system served as the subjects for this study. Utilization and costs between 1999 and 2001 (before and after implementation of open access) were compared for these patients. The main outcome measures were rates of inpatient admissions and various types of outpatient encounters as well as associated costs for these subjects. Between 1999 and 2001, total office visit changes were small and varied with condition, but the proportion of these visits made to primary care physicians increased significantly by an absolute 5% to 9% and primary care physician continuity increased for each condition. Urgent care visits also decreased significantly by an absolute 5% to 9%, but there was no change in emergency department visits or hospital admissions. Total costs of care for these patients were much larger than those for the overall population of the medical group, but increased at a similar rate. A major improvement in patient access to primary care clinics was associated with increased use and continuity of primary care for patients with 3 chronic conditions, but did not affect overall resource use.